Enhanced osteogenic capacity of octacalcium phosphate involving adsorption of stromal-derived factor-1 in a standardized defect of a rat femur - Ryuichi Kanabuchi; Ryo Hamai; Yu Mori; Soshi Hamada; Yukari Shiwaku; Yuko Sai; Kaori Tsuchiya; Toshimi Aizawa; Osamu Suzuki (Journal of Materials Science: Materials in Medicine)
Abstract This study investigated whether octacalcium phosphate (OCP) enhances bone regeneration through its synergistic effect with stromal-derived factor-1 (SDF-1). Recombinant SDF-1 (0.5–5.0 μg) was combined with OCP granules through lyophilization. OCP/SDF-1 granules were implanted into a rat femoral standardized defect for 2 and 4 weeks and subjected to histomorphometry, C-X-C motif chemokine receptor 4 (CXCR4) and osteocalcin immunohistomorphometry, and tartrate-resistant acid phosphatase (TRAP) staining. Calcium-deficient hydroxyapatite (CDHA) was used as a control for in vitro analyses. Mesenchymal stem cell (MSC) migration was estimated using a Transwell system with OCP/SDF-1. SDF-1 release from OCP/SDF-1 into the supernatant was determined without cells. SDF-1 adsorption in 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid buffer onto OCP, the chemical structure of OCP immersed in the medium using Fourier transform infrared spectroscopy, and the degree of supersaturation of the medium were determined. Bone regeneration and OCP degradation were enhanced the most by 1.0 μg of OCP/SDF-1 at 2 weeks after implantation by CT analysis and increasing CXCR4-positive, osteocalcin-positive, and TRAP-positive cells accumulation around the OCP. MSC migration increased until 48 h in the following order: SDF-1 only, CDHA/SDF-1, and OCP/SDF-1, with the greatest effect with 1.0 μg of SDF-1 than from OCP. CDHA promoted a greater release than OCP at 48 h. The physicochemical analyses indicated that SDF-1 interacted with OCP through Freundlich-type adsorption and that the adsorption controlled SDF-1 release from OCP during the hydrolysis into CDHA. Therefore, leveraging its molecular affinity for the OCP surface, OCP/SDF-1 facilitates MSC migration and enhances bone formation by ensuring the controlled, sustained release of SDF-1 from OCP. Graphical Abstract